Policing the near abroad : Russian foreign policy in the South Caucasus - Abushov, Kavus (Routledge, 2009)
This article tries to understand Russia’s policies towards the South Caucasus and answer the question of whether there is a tension between Russia’s interests and policies. An attempt is made to identify Russia’s strategic interests in the region and the crucial factors that shape Russian policies. Based on the assumption that today’s Russia gives de facto support to the secessionist regimes in Georgia, the author attempts to explain what the Kremlin’s motives are in supporting the secessionist regimes. The author investigates whether Russian support for the separatist regimes in the South Caucasus is a reaction to the foreign policy orientation of the parent states or a part of Russia’s security political interests. On the one hand, supporting instability in the South Caucasus cannot be a part of the Kremlin’s strategic interests, because that can pose a threat to the North Caucasus. On the other hand, however, Russian policies are not designed to achieve long-term stability in the South Caucasus, and controlled instability seems to suit the Kremlin. Why Russia vies for coercive hegemony and supports secessionism are the central questions of this article.
Australian Journal of International Affairs.
Keywords: Foreign relations -- Periodicals.; East Asia -- Politics and government -- Periodicals.; World politics -- Periodicals.; Caucasus, South -- Relations -- Russia (Federation).